1983
DOI: 10.1017/s0021859600032561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mulches and antitranspirants on the grain yield of sorghum grown under limited irrigations on a deep vertisol

Abstract: SUMMARYField experiments made for 2 years on a deep vertisol under semi-arid conditions showed that soil-surface evaporation control by mulching with rice straw or transpiration suppression by foliar application of kaolin or atrazine increased the yield of grain sorghum. These materials decreased soil moisture depletion and thus increased water-use efficiency. Application of one irrigation at the boot-leaf stage was beneficial. No additional advantage was noted with two irrigations, one given 45 days after see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…This result is in agreement with De et al (1983) who reported decreased soil moisture depletion and thus increased water use efficiency of rice straw mulch which led to increased yield of grain sorghum. The result also agrees with the findings of Obiefuna (1988) who reported heaviest bunches with the highest number of hands and marketable fingers with sawdust mulch.…”
Section: Discussionsupporting
confidence: 93%
“…This result is in agreement with De et al (1983) who reported decreased soil moisture depletion and thus increased water use efficiency of rice straw mulch which led to increased yield of grain sorghum. The result also agrees with the findings of Obiefuna (1988) who reported heaviest bunches with the highest number of hands and marketable fingers with sawdust mulch.…”
Section: Discussionsupporting
confidence: 93%
“…For semi-arid environments, Agarwal & De (1979) have reported a water-use efficiency of 22 kg barley grain/ha/mm in mulched plots compared with 10 kg grain/ha/mm from unmulched plots. De et al (1983) reported a better soil moisture utilization by field-grown sorghum through mulching or by application of transpiration suppressants. The grain and straw…”
Section: Discussionmentioning
confidence: 99%